Clinically meaningful changes in efficacy outcomes in chronic rhinosinusitis with nasal polyposis. Issue 1 (February 2023) - Mitchell, Margaret B.; Workman, Alan D.; Lee, Stella E.
Abstract : Purpose of review: Chronic rhinosinusitis with nasal polyps (CRSwNP) carries a high disease burden, and many studies have been done investigating the efficacy of various medical and surgical therapies. However, outcome metrics have varied across these studies, making it difficult to compare therapeutic efficacy on a large scale. In this article, we discuss various outcome metrics used across prior studies as well as the relationship between these measures. Recent findings: Outcome metrics in CRSwNP studies include both clinically assessed and patient-reported outcome measures (PROMs). The former includes olfaction testing, scoring systems based on imaging and endoscopic evaluation, and histopathological and immunohistochemical evaluation of sinus tissue, and the latter includes quality-of-life instruments, symptom severity scales, and disease-control instruments. Recent studies evaluating the efficacy of new biologics have used a combination of both types of metrics. Summary: Both clinical metrics and patient-reported outcomes provide utility in evaluating disease severity and control in patients with CRSwNP, although there are nuances when comparing therapies in this population as patients with CRSwNP are heterogeneous and may have symptoms across several domains. However, PROMs in conjunction with clinical metrics provide useful information to assess patient symptoms and response to interventions.